The Politics and Economics of Park Management - Anderson, Terry L.; James, Alexander (Rowman & Littlefield Publishers, 2000)
The Politics and Economics of Park Management examines national protected area systems, in both developed and developing countries, that have made a transformation from 'fortress parks' to a sustainable use model. The contributors—park management, academics, and members of nongovenmental organizations—contend that successful institutional change in protected area systems involves not only the adoption of appropriate legal and regulatory regimes covering sustainable use, but also the development of an informal culture of sustainable resource use among all of a park's stakeholders. While this latter requirement is often difficult to achieve, the contributors show how these informal attitudes may evolve over time, both within the management structure of a park agency and the community of resource users. The case studies cited represent examples of successful institutional change, demonstrating both financial and conservation benefits to protected area agencies, that should serve as model for managing parks today.